Customizable large-scale HPLC fraction collection using low-cost 3D printing - William J. Crandall; Marco Caputo; Lewis Marquez; Zachery R. Jarrell; Cassandra L. Quave (HardwareX)
High-performance liquid chromatography (HPLC) is an invaluable technique that has been used for many decades for the separation of various molecules. The reproducible collection of eluates from these systems has been significantly improved via its automation by fraction collection systems. Current commercially available fraction collectors are not easily customizable, incompatible with other platforms, and come with a large cost barrier making them inaccessible to many researchers. Here we present the efficient construction of a low-cost customizable fraction collector that can easily be paired to any HPLC system. Notably, it supports significantly larger volumes for collection than commercial alternatives. Using a hobbyist-grade three-dimensional (3D) printer (Creality Ender 3 Pro) and aluminum extrusions, the fraction collector can be built for less than $280 USD. An additional graphical user interface (GUI) enables simple programming of the collection methods, requiring no coding experience to operate the collector. The presented fraction collector can be highly customized and use collection vessels as large as 470 mL (80x), facilitating repeated collection at a preparatory scale. The use of this platform will increase the reproducibility of scalable and iterative fraction collection methods while removing the cost barrier and allowing for a high degree of customizability.